2023
DOI: 10.1101/2023.09.04.555897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eta-secretase-like processing of the amyloid precursor protein (APP) by RHBDL4

Penalva Ylauna Christine Megane,
Sandra Paschkowsky,
Sherilyn Junelle Recinto
et al.

Abstract: The amyloid precursor protein (APP) has been extensively studied with regards to its contribution to the pathology of Alzheimer's disease. APP is an ubiquitously expressed type I transmembrane protein synthesized in the endoplasmic reticulum (ER) and translocated to the plasma membrane where it undergoes proteolytic cleavages by several identified proteases. Conversely to other known proteases, we previously elucidated human rhomboid protease RHBDL4 as a novel APP processing enzyme where several cleavages like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 61 publications
2
2
0
Order By: Relevance
“…First, we confirmed our findings that RHBDL4 KO mice show increased endogenous APP levels as compared to WT (Fig. 2C, Penalva et al, 2023). In addition, in the APPtg model, RHBDL4 loss resulted in higher total APP protein expression (Fig.…”
Section: Rhbdl4 Mrna and Protein Expression Levels Are Increased In B...supporting
confidence: 89%
See 3 more Smart Citations
“…First, we confirmed our findings that RHBDL4 KO mice show increased endogenous APP levels as compared to WT (Fig. 2C, Penalva et al, 2023). In addition, in the APPtg model, RHBDL4 loss resulted in higher total APP protein expression (Fig.…”
Section: Rhbdl4 Mrna and Protein Expression Levels Are Increased In B...supporting
confidence: 89%
“…We showed in HEK293T cells that RHBDL4 cleavage of APP led to the production of RHBDL4-specific APP fragments and, decreased cell surface levels of APP and Aβ production . We further confirmed that RHBDL4 cleavage of APP occurs in primary mixed cortical cultures (Penalva et al, 2023). Specifically, we found that RHBDL4 knockout (R4 KO) mixed cortical cultures did not produce an RHBDL4-specific APP fragment termed "Aη-like" for its resemblance to the APP fragment originally described to be produced by MT5-MPP by Willem et al (Penalva et al, 2023;Willem et al, 2015).…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations